ANALISIS HUBUNGAN TINGKAT PENGETAHUAN, FREKUENSI PEMBERIAN PROMOSI KIE DAN MINAT PADA IUD PASCA PLASENTA DENGAN PENGGUNAAN METODE KB PADA BIDAN DI KABUPATEN LOMBOK TENGAH - Rahmawati, Trisna Anesa; Sastrawan, Sastrawan (Midwifery Journal: Jurnal Kebidanan UM. Mataram, 2024)
Abstract: Midwives play a pivotal role as influential figures in endorsing the adoption of contraceptive methods, concurrently engaging in the promotion and dissemination of Information, Education, and Communication (IEC) to Women of Childbearing Age (WUS). Consequently, the knowledge, attitudes, and practices exhibited by midwives wield considerable influence over the decision-making processes of expectant mothers concerning their pregnancies and childbirth. Research Objective: The primary aim of this study is to scrutinize the interplay between midwives' knowledge, interest in post-placental intrauterine device (IUD), and their IEC promotional efforts in relation to the selection of contraceptive methods within the midwifery community in Central Lombok Regency. Methodology: Employing an analytical survey with a cross-sectional design, this research encompassed a study population of 1201 individuals, with a specific sample size of 218. Data acquisition was carried out through the utilization of a Google Form. Findings: A statistically significant correlation was identified between midwives' interest in post-placental IUD and the utilization of IUD contraceptive methods (p-value=0.002). Conversely, no discernible relationship was observed between the proficiency of midwives' knowledge and their promotional and IEC activities and the adoption of IUD contraceptive methods. Conclusion: The study concludes that midwives' expressed interest in post-placental IUD is notably associated with the prevalent use of IUD contraceptive methods among midwives in Central Lombok Regency.Abstrak: Bidan dapat bertindak sebagai role model dalam penggunaan metode kontrasepsi sekaligus dapat memberikan promosi dan pemberi KIE kepada WUS. Dengan demikian pengetahuan, sikap dan Tindakan bidan dapat berpengaruh terhadap keputusan ibu hamil dalam kaitannya dengan kehamilan dan kelahirannya. Tujuan Penelitian: Untuk menganalisis hubungan pengetahuan bidan, minat bidan pada IUD pasca plasenta dan tindakan promosi KIE dengan pilihan metode KB pada bidan di kabupaten lombok Tengah. Metode: Penelitian menggunakan survey analitik dengan rancangan cross sectional. Populasi penelitian ini adalah 1201 orang dengan sampel sebanyak 218 orang Peneliti mengumpulkan data menggunakan google form. Hasil penelitian: Terdapat hubungan yang signifikan antara minat bidan terhadap IUD pasca plasenta dengan penggunaan metode KB IUD (p value=0,002). Tidak ada hubungan tingkat pengetahuan bidan serta tindakan promosi dan KIE dengan penggunaan metode KB IUD Kesimpulan: Minat bidan terhadap IUD pasca plasenta berhubungan signifikan dengan penggunaan metode KB IUD pada bidan di Kabupaten Lombok Tengah.